It is Necessary to Develop an Assessment System that all Students can accept at the Universitas Negeri Malang: An Editorial Board Report - Ediyanto Ediyanto; Mohammad Efendi (Department of Special Education, 2021)
A total of 36 Students with Special Needs (SEN) spread across all faculties prove their acceptance at the State University of Malang (UM). However, there has been no assessment tailored to the student’s needs or is still done traditionally. Therefore, it is necessary to develop an assessment tailored to students’ special needs, help lecturers gather information, facilitate the decision-making process, and make fair assessments. In addition, by an appropriate assessment system, student understanding can be assessed in various ways and accurately measure student success rates. This study aims to develop formative and summative assessments for SEN in UM. Due to the pandemic conditions and research methods, the assessment developed will be implemented online.